2022
DOI: 10.1109/lsp.2022.3169428
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid SFANC-FxNLMS Algorithm for Active Noise Control Based on Deep Learning

Abstract: The selective fixed-filter active noise control (SFANC) method selecting the best pre-trained control filters for various types of noise can achieve a fast response time. However, it may lead to large steady-state errors due to inaccurate filter selection and the lack of adaptability. In comparison, the filtered-X normalized least-mean-square (FxNLMS) algorithm can obtain lower steady-state errors through adaptive optimization. Nonetheless, its slow convergence has a detrimental effect on dynamic noise attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Through the proposed algorithm, it was confirmed that the LSTM is capable of noise cancellation for diesel engine noise different from the training data (different fundamental frequency, superposed harmonic sound, engine start noise) in the linear system. Recently, there are various studies on advanced ANC algorithms using deep neural networks [14,15,26,27]. Comparing the performance of advanced ANC algorithms in practical applications is a future task.…”
Section: Anc Simulation Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the proposed algorithm, it was confirmed that the LSTM is capable of noise cancellation for diesel engine noise different from the training data (different fundamental frequency, superposed harmonic sound, engine start noise) in the linear system. Recently, there are various studies on advanced ANC algorithms using deep neural networks [14,15,26,27]. Comparing the performance of advanced ANC algorithms in practical applications is a future task.…”
Section: Anc Simulation Results and Discussionmentioning
confidence: 99%
“…Through the use of a 10-layer extended convolutional neural network (CNN) on a field-programmable gate array, a real-time streaming feedforward ANC system for in-ear headphones was shown in a practical application scenario [14]. A hybrid selective fixed-filter active noise control (SFANC) and filtered-X normalized least-mean-square (FxNLMS) approach was proposed to overcome the adaptive algorithm's slow convergence and provide a better noise reduction level using deep learning [15]. Another study presented a neural-based FxLMS with an error backpropagation algorithm to cancel non-linear broadband noise in an ANC system [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The GFANC algorithm is compared to SFANC [27] and FxLMS in controlling real-world noises, which do not belong to the training dataset. The step size of FxLMS algorithm is 0.0001.…”
Section: Real-world Noise Cancellationmentioning
confidence: 99%
“…The results indicate that the control filter generated by the GFANC method is more suitable for the noise than that provided by the SFANC method. Furthermore, our previous research [27] demonstrated that combining fixed-filter and adaptive ANC algorithms can achieve rapid convergence and satisfactory noise reduction level.…”
Section: Real-world Noise Cancellationmentioning
confidence: 99%
“…The controller then adjusts the control filter coefficients based on the received filter index. Notably, if the network is a 1D CNN, its input is the raw waveform [14]. However, if the network is a 2D CNN, its input is the Log Mel-spectrogram [15].…”
Section: Cnn-based Sfanc Algorithmmentioning
confidence: 99%